Computer Lab Information System : Team E Wave 2008 - Jantan, Azizi; Jaafar, Ahmad Faizar; Sulaiman, Muhammad Azmir; Jaafar, Ahmad Nazri (Perpustakaan Tun Abdul Razak, 2008)
CLIS utilizes electronic registration system to ensure that the registration record can be stored in an electronic database for the purpose of generating on-line statistic record wich is accessible at all times, fast and accurate. CLIS is an online IT lab management system that works systematically through online access available all over UiTM Malaysia Library and UiTM Branch Campuses Library.